2009
DOI: 10.1111/j.1524-475x.2009.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of functional sweat gland‐like structures by transplanted differentiated bone marrow mesenchymal stem cells

Abstract: Regeneration of sweat glands after deep burns has been an unsolved problem. Owing to lack of perspiration, survivors of an extensive deep burn injury are leading a miserable life in sultry months. It was our contemplation to solve this problem by inducing bone marrow mesenchymal stem cells (MSCs) to acquire the phenotype of sweat gland cells in vitro. Then these cells were transplanted into fresh skin wounds resulting from excision of anhydrotic scars after healing of deep burn injury in five patients. Two to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 18 publications
(26 reference statements)
1
89
0
1
Order By: Relevance
“…The MSCs transformed into sweat gland cells and facilitated the recovery of functional sweat glands. This phenomenon may help address the problem of sweat gland depletion in patients surviving extensive deep burns (64). The WJMSCs, in a specific induction system, may hopefully differentiate into sweat gland cell-like cells.…”
Section: Wharton's Jelly Multipotent Stem Cells and Skin Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSCs transformed into sweat gland cells and facilitated the recovery of functional sweat glands. This phenomenon may help address the problem of sweat gland depletion in patients surviving extensive deep burns (64). The WJMSCs, in a specific induction system, may hopefully differentiate into sweat gland cell-like cells.…”
Section: Wharton's Jelly Multipotent Stem Cells and Skin Reconstructionmentioning
confidence: 99%
“…The regeneration of sweat glands, after deep burns, has been an unresolved challenge. To address this problem, our group previously induced BMMSCs to acquire the phenotype of sweat gland cells in vitro and then transplanted them into fresh skin wounds, made by excising the anhidrotic scars of five patients after their deep burn injuries were healed (64). The MSCs transformed into sweat gland cells and facilitated the recovery of functional sweat glands.…”
Section: Wharton's Jelly Multipotent Stem Cells and Skin Reconstructionmentioning
confidence: 99%
“…They are defined by their fibroblast-like morphology and capacity for osteogenic, chondrogenic, and adipogenic fates in vitro [13]. MSCs have also been reported to regenerate functional sweat glands, which may help to solve the problem of sweat gland depletion in patients surviving extensive deep burns [4]. Easy access to large quantities is an advantage of adipose-derived stem cells that are being tested for soft-tissue repair and regeneration.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Figure1 summarizes the approved projects and funding from the NSFC for stem cell-based research and trials, and the related articles published in Science Citation Index journals from 2008 to 2012. These achievements involved preclinical studies of stem cells and tissue engineering products for coronary heart diseases, diabetes, liver failure, sweat gland injury after burns, and other serious diseases, which establish a solid foundation for clinical application and industrialization of future products [3][4][5][6][7][8]. However, the therapeutic market for stem cell applications is not mature enough in China, resulting in a lack of large-scale market-oriented stem cell-based products.…”
Section: Frontline Innovationsmentioning
confidence: 99%
“…For example, chemotherapeutic agents or glucocorticoids were applied within one week of immune cell transfusion. Overall, fewer than 50 cases with integrated laboratory and clinical data were available for analysis (Yang et al, 2012;Lu et al, 2012;Wang et al, 2013;Sheng et al, 2009). Our five-year practice revealed that this CPC-centered and multidisciplinary collaborative translational approach provided a high-input, low-output model, at least under the current conditions of Chinese hospitals.…”
mentioning
confidence: 99%